The Effect of Capital Adequacy on Returns of Assets of Commercial Banks in Kosovo - Shabani, Halit; Morina, Fisnik; Misiri, Valdrin (European Journal of Sustainable Development, 2019)
The purpose of this study is to analyze the effects of capital adequacy on the return of assets to the banking sector in Kosovo. The capital adequacy ratio measures the ability of a financial institution to meet its liabilities by comparing its capital with its assets. As the banking system is one of the strongest points of our country's economy, it is understood that the capital adequacy ratio is used by banks to determine the adequacy of their capital holdings while taking their risk exposures into account. This study will provide empirical evidence of the relationship between capital adequacy and return on commercial bank assets in Kosovo during 2008-2017. It will be using secondary data obtained from audited reports of domestic banks and reports from the Central Bank of Kosovo. To measure the empirical results during this research, these econometric methods have been used: the linear regression model, the model of the fixed effects, and the random model and the GMM model. Based on the results we can conclude that capital adequacy has a positive impact on asset returns and has a significant relationship. In addition, other factors have had a positive and negative impact on the return of commercial banks' assets in Kosovo. Keywords: capital adequacy, return on assets, loans, deposits, interest rates. JEL Classification: G21, G31, G32